Mysterious eye of the dragon - Stilton, Geronimo (Stilton, Geronimo, Geronimo Stilton, 2021)
"My sister Thea and my cousin Trap were not getting along! When Grandfather found them arguing over who would get to join me on a trip to Brazil, he forced us all to go together. My friend Isabela needed my help finding a mysterious emerald. Could Trap and Thea stop shouting their snouts off long enough to help find the stone?" -- Back cover.